Use of 4β-hydroxycholesterol in animal and human plasma samples as a biomarker for CYP3A induction. (February 2016) - Xue, Y-J; Hoffmann, Matthew; Tong, Zeen; Wu, Xinqun (Irene); Vallejo, Martha; Melo, Brian; Ye, Ying; Thomas, Michael; Liu, Yong; Weiss, Daniel; Surapaneni, Sekhar
Background: 4β-hydroxycholesterol (4βHC) has recently been proposed as a potential endogenous biomarker for CYP3A activity. Developing bioanalytical assays for 4βHC is challenging for several reasons, including endogenous background levels in plasma; the presence of free and ester forms; the inherent lack of MS sensitivity; and the presence of multiple positional isomers.Results: Bioanalytical assays in mouse, rat, dog and human plasma were adapted and modified from a previous published human plasma assay for 4βHC by using alkaline de-esterification, picolinic derivatization, a surrogate analyte ( d 7-4βHC) in authentic matrices and chromatographic conditions that showed good separation from isobaric, positional isomers.Conclusion: These assays were applied to multiple studies and demonstrated potential applications of 4βHC as a CYP3A biomarker across preclinical and clinical settings.